Manajemen Kurikulum - Miftah Syahrul Ramadhan; Suklani (Jurnal Dirosah Islamiyah, 2024)
Curriculum management is a curriculum management system that is comprehensive and systematic in order to realize curriculum achievement. A curriculum that is considered good is a curriculum that follows developments in science and technology in society. Curriculum empowerment determines achievement and failure in education. Therefore, this It is the responsibility of educational institutions and all stakeholders must have the same goals in planning, organizing, implementing and evaluating the curriculum.